Two-dimensional vortex ring studies - Teo, Derek Chong Ren. (2011)
This project aims to conduct a study on two-dimensional vortex rings formation. The generation of the vortex rings was conducted in the Water Tunnel Facility using a rectangular and a circular orifice. Both the height of the rectangular orifice slot and the diameter of the circular orifice slot were designed to be 40 mm. A pitot static tube was used to measure the actual velocity of the fluid flow through the orifices and the speed of the Water Tunnel was adjusted accordingly to achieve a Reynolds number of 5000. The formation of the vortex pair/rings were visualized with ink dye with the aid of a syringe pump. The results were analyzed and it has indicated that the formation of the vortex pair from the rectangular orifice was steady. Instability was observed from the formation of the vortex rings from the circular orifice.